Perubahan Pengaturan Pendirian Perseroan Terbatas Pasca Disahkan UU Cipta Kerja - Pratama, Dian Putri; Turisno, Bambang Eko (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2023)
AbstractGovernment has enacted Government Regulation No. 8 of 2021 as the implementation regulation of Job Creation Act that has brought several changes to Law No. 40 of 2007. PP No. 8/2021 amends several provisions in UU PT such as Authorized Capital, Registration of Establishment, Amendment, and Disbanding of One-Person Company that meet the criteria for Micro and Small Business (UMK). This research employs a normative-descriptive approach and aims to discuss the significant amendment of provisions in UU PT as stipulated in PP No. 8 /2021. The amendment of UU PT covers (i) the abolition of provision regarding minimum Authorized Capital, (ii) provision regarding “One-Person Company”, including technical regulation of Establishment, Amendment, and Disbanding of One-Person Company, and also the obligation to make and submit a financial report. Keywords : establishment of individual companies; uu create workAbstrakPemerintah saat ini telah mengesahkan Peraturan Pemerintah No. 8/Tahun 2021, guna menjadi peraturan pelaksana atas Regulasi Cipta Kerja yang telah mengubah Regulasi Undang-Undang Perseroan Terbatas No. 40/Tahun 2007. PP No. 8/2021 mengatur mengenai perubahan ketentuan dalam UUPT, antara lain: Modal Dasar, Pendaftaran Pendirian, Perubahan, dan Pembubaran Perseroan Perorangan dengan kriteria UMK (Usaha Mikro dan Kecil). Metode yuridis normatif-deskriptif akan digunakan dalam Penelitian ini fokus dan membahas perubahan yang cukup signifikan mengenai regulasi UU PT yang diatur dalam PP No. 8/2021. Poin signifikan yang diubah dalam UU PT. adalah aturan penghapusan ketentuan batasan minimum Modal Dasar UU PT; dan aturan baru perihal “Perseroan Perorangan”, termasuk aturan teknis mendirikan, mengubah, dan membubarkan Perseroan perorangan, serta keharusan membuat dan menyampaikan laporan keuangan.Kata kunci: pendirian perseroan perorangan; uu cipta kerja